FAMILY SUPPORT AND COPING STRATEGIES IN FERTILITY TREATMENT: A HOLISTIC EXAMINATION - Maccabi, Leila Cohen; Maccabi, Amirah Levy Maccabi; Maccabi, Yael Ben-David (Research Journal of Health, Medicine and Nursing, 2024)
Infertility is a significant global health concern, and its prevalence has increased in recent years, affecting approximately 10%–15% of heterosexual couples with women of childbearing age. This paper explores the various dimensions of infertility, including its emotional and societal implications, particularly in the context of evolving family structures and societal expectations.